Analisis Faktor-Faktor yang Mempengaruhi Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Karangasem - Agung, Tut Madiguna; ., Gayatri (E-Jurnal Akuntansi; Vol 23 No 2 (2018), 2018)
The phenomenon in the development of the public sector in Indonesia is the strengthening of the demand for the quality of government financial reports. The resulting government financial report must meet the qualitative characteristics of Government Regulation No. 71 of 2010. The study was conducted on SKPD Kabupaten Karangasem which amounted to 43 SKPD in the Government of Karangasem Regency. The number of samples taken as many as 129 people. The analysis technique used is multiple linear regression analysis. The results showed leadership style, human resource competence, internal control system, organizational commitment and utilization of information technology have a positive and significant impact on the quality of local government financial statements. The researcher is then expected to be able to add other factors that may affect the quality of local government financial statements, such as adding independent variables or moderating variables such as the application of government accounting standards.